2006
DOI: 10.1063/1.2162667
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and cathodoluminescence analyses of GaN powder doped with Eu

Abstract: A high yield process to produce gallium nitride (GaN) powder doped with europium (Eu) is presented. Eu is in situ incorporated into GaN powder through the reaction between a molten alloy of Ga and Eu along with NH3 at 1000 °C using Bi as a wetting agent. This procedure provides a method to produce a GaN:Eu phosphor with high yield and low cost. Room temperature photoluminescence (PL) measurements are studied on GaN:Eu powders with different Eu concentrations. The maximum PL intensity is obtained at a Eu concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…Up to now, the few reported work on Eu doped GaN powders include a combustion method [3]; ammonolysis of the freeze-dried [4]; and a two-stage vapor phase method [5], etc. Recently, we developed a simple, low-cost, and high-yield process to convert Ga to high quality GaN using Bi as a wetting agent, and Er, Eu doping has been achieved [7,8,10]. In this paper, we report the effect of the growth temperature on the effective incorporation of Eu in GaN powders.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Up to now, the few reported work on Eu doped GaN powders include a combustion method [3]; ammonolysis of the freeze-dried [4]; and a two-stage vapor phase method [5], etc. Recently, we developed a simple, low-cost, and high-yield process to convert Ga to high quality GaN using Bi as a wetting agent, and Er, Eu doping has been achieved [7,8,10]. In this paper, we report the effect of the growth temperature on the effective incorporation of Eu in GaN powders.…”
mentioning
confidence: 99%
“…Though doping of Eu, Er, Tm and other RE elements in GaN either in-situ or by implantation has been achieved by several groups [2], GaN in most cases is in the form of films produced by MBE, CVD or sputtering, etc. There exists much less work exists on rare earth doped GaN powders [3][4][5][6][7][8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Park and Steckl reported that two different Eu 3+ sites are involved in stimulated emission (lasing) in W-GaN:Eu optical cavities [5]. A reported blue-shift of the dominant Eu 3+ peak in W-GaN powder, to 611 nm, ascribed to the existence of stacking faults and cubic structures [6], was not reproduced in later work [7]; moreover, aggregation of nanocrystalline powder into micrometer-sized conglomerates reportedly causes a significant red-shift of Eu 3+ emission spectra [8]. Despite many investigations, the luminescence spectroscopy of RE-doped GaN and the energy transfer from the wide bandgap host to the optically active RE centres are not well understood.…”
mentioning
confidence: 94%